Promotion of Cell Cycle Progression by Basic Helix-Loop-Helix E2A - Zhao, Fang (American Society for Microbiology, 2001)
Normal B-cell development requires the E2A gene and its encoded transcription factors E12 and E47. Current models predict that E2A promotes cell differentiation and inhibits G(1) cell cycle progression. The latter raises the conundrum of how B cells proliferate while expressing high levels of E2A protein. To study the relationship between E2A and cell proliferation, we established a tissue culture-based model in which the activity of E2A can be modulated in an inducible manner using E47R, an E47-estrogen fusion construct, and E47ERT, a dominant negative E47-estrogen fusion construct. The two constructs were subcloned into retroviral vectors and expressed in the human pre-B-cell line 697, the human myeloid progenitor cell line K562, and the murine fibroblastic cell line NIH 3T3. In both B cells and non-B cells, suppression of E2A activity by E47ERT inhibited G(1) progression and was associated with decreased expression of multiple cyclins including the G(1)-phase cyclin D2 and cyclin D3. Consistent with these findings, E2A null mice expressed decreased levels of cyclin D2 and cyclin D3 transcripts. In complementary experiments, ectopic expression of E47R promoted G(1) progression and was associated with increased levels of multiple cyclins, including cyclin D2 and cyclin D3. The induction of some cyclin transcripts occurred even in the absence of protein synthesis. We conclude that, in some cells, E2A can promote cell cycle progression, contrary to the present view that E2A inhibits G(1) progression.